Monometallic and multimetallic complexes as precatalysts in the hydroformylation of olefins - Siangwata, Shepherd (Department of Chemistry, 2020)
A series of new aryl ether salicylaldimine-based monomeric, dimeric, trimeric and hexameric triazolyl ligands have been synthesised. The N,O-chelating ligands were synthesised via Schiff base condensation reactions of salicylaldehyde with the bromopropylamine hydrobromide salt, followed by the azidation of the resultant N-3-bromopropylsalicylaldimine. Click chemistry reactions of the azido propyl salicylaldimine with the appropriate phenolic-alkyne afforded the mono-, di-, tri- and hexameric aryl ether salicylaldimine-based triazolyl ligands. The ligands were characterised using various analytical and spectroscopic techniques. Complexation of the monomeric and trimeric ligands with the dimeric rhodium precursor [RhCl(COD)]2 yielded new aryl ether N,O-chelate mononuclear and trinuclear Rh(I) complexes. The complexes were characterised using nuclear magnetic resonance spectroscopy, infrared spectroscopy, mass spectrometry and melting point determinations. The mononuclear and trinuclear complexes were successfully evaluated as catalyst precursors in the hydroformylation of higher olefins. The reaction conditions were optimised using the mononuclear precatalyst at 85 ℃, 40 bar syngas pressure for 4 h with 2.87 x 10-3 mmol Rh loading and a substrate (1-octene) to catalyst ratio of 2500 : 1. These conditions gave good aldehyde chemoselectivity (90%), excellent conversion of the substrate (99%) and good catalytic activity (554 h-1 ). Comparable catalytic performance of both precatalysts was obtained when milder reaction conditions (85 ℃, 20 bar for 4 h) were adopted in the evaluation of the mononuclear complex against the low generation dendritic trinuclear complex. The mercury poisoning experiments revealed a dual catalytically influenced system, emanating from a combination of homogeneous and heterogeneous catalytic species. The mononuclear catalyst precursor was also evaluated successfully in the hydroformylation of internal olefins 7- tetradecene and trans-4-octene. The catalyst precursor gave good conversions of both internal olefins (> 80%) under the optimum reaction conditions (85 ℃, 40 bar for 4 h). Catalyst recyclability studies in the hydroformylation of 1-octene conducted using the Organic Solvent Nanofiltration (OSN) strategy demonstrated five successful recycles with consistently good catalytic performance from both catalyst precursors. Inductively coupled plasma optical emission spectrometry (ICP-OES) experiments revealed a near perfect (99%) membrane retention of the rhodium metal. Kinetic studies using the mononuclear precatalyst were investigated by evaluating the effect of temperature, syngas total pressure and catalyst loading on the rate of hydroformylation. The activation energy for the hydroformylation of 1-octene was calculated to be 62 kJ mol-1 and the experimental rate constants were found to be in good agreement with the predicted rate data obtained using a modified fundamental mechanismbased rate model. The synthesis and characterisation of new water-soluble, sulfonated aryl ether salicylaldiminebased mono- and trimeric ligands has also been described. The ligands were prepared following a series of amine and Boc-protection and deprotection procedures, Schiff base condensation reactions and Williamson ether synthesis. The water-soluble N,O-chelating aryl ether ligands were characterised using various spectroscopic and analytical techniques. Subsequently, complexation reactions of the ligands with the dimeric [RhCl(COD)]2 gave the corresponding new water-soluble mononuclear and trinuclear Rh(I) complexes. The complexes were characterised using nuclear magnetic resonance spectroscopy, infrared spectroscopy, mass spectrometry and melting point determinations. The complexes show appreciably good solubility in water, 15.7 mg/mL (mononuclear complex) and 8.6 mg/mL (trinuclear complex). The new water-soluble mono- and trinuclear complexes were successfully evaluated as precursors in the aqueous biphasic hydroformylation of higher olefins. Optimisation experiments using the mononuclear precatalyst gave the best results at 85 ℃, 50 bar syngas pressure for 4 h with 2.87 x 10-3 mmol Rh loading and a substrate (1-octene) to catalyst ratio of 2500 : 1. Both catalyst precursors gave near quantitative catalytic conversion of 1-octene, good activities (> 550 h -1 ) and attractive aldehyde chemoselectivity (> 85%). A substrate and product-distribution time study showed a positive dendritic effect in relation to the trinuclear complex over the mononuclear complex. The mercury poisoning experiments were suggestive of a system that is catalysed by a dual effect of homogeneous and heterogeneous catalytic species. Recyclability experiments were successfully conducted over 5 cycles, with a gradual decline in catalytic performance for both complexes. The dendrimer stabilised trinuclear precatalyst showed improved recyclability in “neat”, monophasic hydroformylation experiments, while the mononuclear precatalyst showed a reduced overall performance. The bias towards the linear aldehyde for the dendritic trinuclear complex was tunable by addition of excess bulkier trimeric water-soluble ligand into the catalytic system. Inductively coupled plasma optical emission spectrometry experiments showed moderate losses of the metal from the aqueous phase to the organic layer. Both catalyst precursors also showed good catalytic activity (> 450 h-1 ) and a total bias to aldehyde chemoselectivity (no hydrogenation products) in the aqueous biphasic hydroformylation of styrene.